CAN INDEPENDENT COMMISSIONERS SERVE AS CORPORATE GATEKEEPERS IN MITIGATING THE IMPACT OF FINANCIAL AGGRESSIVENESS ON TAX BEHAVIOR? - Zakiah Zakiah; Nurul Aisyah Rachmawati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
This study examines the relationship between financial and tax aggressiveness, using independent commissioners as a moderating variable. It employs a quantitative method with purposive sampling. The population includes energy sector companies listed on the Indonesia Stock Exchange from 2020 to 2022. The study aims to determine how financial aggressiveness impacts tax aggressiveness and how independent commissioners influence the relationship between the two. The results show that financial aggressiveness significantly negatively affects tax aggressiveness, while independent commissioners have no impact on the relationship between financial and tax aggressiveness.